Menstrual Hygiene Practice and School Absenteeism among Rural Adolescent girls of Kalikot district (Nepal Medical College Journal, 2019)
Menstruation is a part of female reproductive cycle that starts when girls become sexually mature at the time of puberty. This study sought to assess the menstrual hygiene practice and school absenteeism among the rural school going adolescent girls. A descriptive cross-sectional study was done among 321 female high school students of 4 selected government schools of Kalikot a rural district of Nepal. It was found that majority of student’s menstrual hygiene practice was poor i.e. 86.9%. Majority of respondents (96 %) used clean cloth during their menstruation cycle, whereas only 4% of respondents used sanitary pad. Almost every adolescent girl i.e. 98.8 % practiced any cultural restriction. Nearly 1 in 4 respondents (22.1%) did not attend school during their last menstruation and more than 1 in 10 adolescent girls felt that their academic performance was degraded after menarche. Adolescent girls of 10-14 age group were three time more likely to have poor practice than those who were between 15-19 years. Adolescent girls from nuclear families are 1.9 times more likely to be absent from school during the menstrual cycle in comparison to girls from joint families. The study revealed that among the adolescent girls of the study area, the overall menstrual hygiene practice was found to be poor and the various beliefs were found to be inappropriate and school absenteeism was also prevalent during menstrual cycle.